DAKHîL AL-ISRâ’ILîYâT KISAH NABI YûSUF DALAM AL-JâMI‘ LI AHKâM AL-QUR’âN KARYA AL-QURTUBî - Amrullah Hafizh, Azhar (Program Studi Perbandingan Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2015)
Normatively, the Prophet Muhammad is not giving a ban to tell tales originating from the Banî Isrâ?îl. The Prophet simply gave the record that his people did not justify and deny the stories narrated by Ahl al-Kitâb. However, in the course of the history of Islam, many isrâ?ilîyât seeps into some sort of authoritative books of Jâmi? al-Bayân created by al-Tabarî, Tafsîr al-Qur?ân al-?Azîm by Ibn Kathîr, Rûh al-Ma?ânî by al-Alûsî, and al-Jâmi? li Ahkâm al-Qur?ân by al-Qurtubî. Ironically, in many cases, isrâ?ilîyât that goes into the book of commentary of the Koran without any comments from the authors, so it assumes that the isrâ?ilîyât is a strong opinion and can be used as a reference. As a result, isrâ?ilîyât like virus that continues to undermine the authenticity of the Koran